Tech mining: a revisit and navigation - Porter, Alan L.; Zhang, Yi; Newman, Nils C. (Frontiers in Research Metrics and Analytics, 2024)
This mini-review arrays the pertinent tools and purposes of "Tech Mining" --shorthand for empirical analyses of Science, Technology & Innovation (ST&I) data. The intent is to introduce the range of tools, and show how they can complement each other. Tech Mining aims to generate powerful intelligence to help manage R&D and innovation processes. We offer a 5-part array to help relate the analytical elements. An overview of a case study of Hybrid & Electric Vehicles illustrates the complexities involved and the potential to generate valuable "intel.